Influence of Fluoride-Resistant Streptococcus mutans Within Antagonistic Dual-Species Biofilms Under Fluoride In Vitro - Zhang, Keke; Xiang, Yangfan; Peng, Youjian; Tang, Fengyu; Cao, Yanfan; Xing, Zhenjie; Li, Yejian; Liao, Xiangyan; Sun, Yan; He, Yan; Ye, Qingsong (Frontiers in Cellular and Infection Microbiology, 2022)
The widespread application of fluoride, an extremely effective caries prevention agent, induces the generation of fluoride-resistant strains of opportunistic cariogenic bacteria such as fluoride-resistant Streptococcus mutans (S. mutans). However, the influence of this fluoride-resistant strain on oral microecological homeostasis under fluoride remains unknown. In this study, an antagonistic dual-species biofilm model composed of S. mutans and Streptococcus sanguinis (S. sanguinis) was used to investigate the influence of fluoride-resistant S. mutans on dual-species biofilm formation and pre-formed biofilms under fluoride to further elucidate whether fluoride-resistant strains would influence the anti-caries effect of fluoride from the point of biofilm control. The ratio of bacteria within dual-species biofilms was investigated using quantitative real-time PCR and fluorescence in situ hybridization. Cristal violet staining, scanning electron microscopy imaging, and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide assay were used to evaluate biofilm biomass, biofilm structure, and metabolic activity, respectively. Biofilm acidogenicity was determined using lactic acid and pH measurements. The anthrone method and exopolysaccharide (EPS) staining were used to study the EPS production of biofilms. We found that, in biofilm formation, fluoride-resistant S. mutans occupied an overwhelming advantage in dual-species biofilms under fluoride, thus showing more biofilm biomass, more robust biofilm structure, and stronger metabolic activity (except for 0.275 g/L sodium fluoride [NaF]), EPS production, and acidogenicity within dual-species biofilms. However, in pre-formed biofilms, the advantage of fluoride-resistant S. mutans could not be fully highlighted for biofilm formation. Therefore, fluoride-resistant S. mutans could influence the anti-caries effect of fluoride on antagonistic dual-species biofilm formation while being heavily discounted in pre-formed biofilms from the perspective of biofilm control.